The Influence of Brand Image and Online Customer Reviews on Consumer Purchasing Decisions at the Shopee Marketplace in Surabaya - Dani Fajariyatusyarifah; Ugy Soebiantoro (PT Inovasi Pratama Internasional, 2023)
This research aims to analyze the influence of each Brand Image and Online Customer Review on Purchasing Decisions at the Shopee Marketplace in Surabaya. The population in this research is consumers who buy products on the Shopee marketplace with a sample of 108 respondents and was determined using a non-purposive sampling technique. Primary data was obtained using questionnaires while secondary data was obtained using books, journals, literature and websites or the internet. Based on the test results using SMARTPLS, it was found that this research shows that all indicators are valid or all variables are significantly positive for purchasing decisions. Based on the Outer Loading results, the estimation results for all indicators have met convergent validity or good validity. Based on the results of the AVE test as a whole, the variables in this study can be said to have good validity. Based on the results of the Composite Reability test, it is said that all the variables in this study are reliable.